2001
DOI: 10.1093/clinchem/47.3.459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Implantable Cardioverter Defibrillator Implantation and Shock Application on Biochemical Markers of Myocardial Damage

Abstract: Background: Implantable cardioverter defibrillator (ICD) implantation is a common approach in patients at high risk of sudden cardiac death. To check for normal function, it is necessary to test the ICD. For this purpose, repetitive induction and termination of ventricular fibrillation by direct current shocks is required. This may lead to minor myocardial damage. Cardiac troponin T (cTnT) and I (cTnI) are specific markers for the detection of myocardial injury. Because these proteins usually are undetectable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 12 publications
2
26
0
1
Order By: Relevance
“…Indeed, patients with left ventricular dysfunction had higher baseline IMA values compared to those with preserved systolic function; this may be one of the reasons that IMA changes are blunted in the ICD group versus the PPM group, the other reason being the fact that PPM patients are on paced rhythm after the completion of the procedure with subsequent altered depolarization and possibly subendocardial ischemia whereas ICD patients are usually on their intrinsic rhythm. Minimally elevated troponin concentrations, reflecting minor myocardial injury, have also been described following transvenous ICD implantation, [20][21][22] but this has been mainly attributed to the induction and termination of VF episodes during testing. However, the only study that included a control group with similar threshold testing and generator replacement but without electrode insertion, did not find a detectable increase in troponin whereas it did show a modest but significant increase in its levels following transvenous ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with left ventricular dysfunction had higher baseline IMA values compared to those with preserved systolic function; this may be one of the reasons that IMA changes are blunted in the ICD group versus the PPM group, the other reason being the fact that PPM patients are on paced rhythm after the completion of the procedure with subsequent altered depolarization and possibly subendocardial ischemia whereas ICD patients are usually on their intrinsic rhythm. Minimally elevated troponin concentrations, reflecting minor myocardial injury, have also been described following transvenous ICD implantation, [20][21][22] but this has been mainly attributed to the induction and termination of VF episodes during testing. However, the only study that included a control group with similar threshold testing and generator replacement but without electrode insertion, did not find a detectable increase in troponin whereas it did show a modest but significant increase in its levels following transvenous ICD implantation.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with coronary artery disease, hypotension due to prolonged episodes of VF may result in myocardial ischemia. Perioperative myocardial infarction is difficult to diagnose because routine defibrillation testing 190 shocks delivered for spontaneous VT/VF or supraventricular tachycardia may cause both elevation of troponin 191 and non-specific ECG changes. However, in an analysis of shocks for spontaneous arrhythmias, tro-ponin elevations were both more likely and higher in patients with coronary artery disease than in those without, 192 suggesting that the combination of VT/VF and shocks causes ischemic injury in some patients.…”
Section: Myocardial Ischemia and Electromechanical Dissociationmentioning
confidence: 99%
“…The myocardial damage induced by defibrillation shocks seems to be related to the shock energy delivered. [3][4][5][6][7] The 100 V/0.12-ms field stimulus contains only 0.1% of the energy of a ≥20-J high-energy shock. Therefore, a therapy strategy for VT including field stimuli after failed ATP before the delivery of high-energy shocks may be less damaging to the heart 3-7 than the direct application of a high-energy shock after failed ATP.…”
Section: Discussionmentioning
confidence: 99%
“…High-energy shocks from implantable cardioverter-defibrillators (ICDs) reliably terminate any kind of ventricular tachyarrhythmia. 1,2 There have been many attempts to reduce unnecessary shocks, mainly because of the pain they cause and battery consumption, but also because of reports of myocardial damage [3][4][5][6][7] after ICD shocks. The relevance of this last aspect has been highlighted by a recent study that suggested that paradoxically, although they are lifesaving, appropriate ICD shocks for ventricular arrhythmia increase mortality, probably by influencing heart-failure mechanisms.…”
Section: Introductionmentioning
confidence: 99%